The stratum [videorecording (DVD)] - Buist, Crash; Buist, Crash; Senechal, Lauren; Senechal, Lauren; Carr, Wayne T; Medina, Jonathan; Karimloo, Ramin, 1978- (Vision Films, 2023)
In a dystopian future, a deadly virus devastates the planet. The greedy CEO of a tech conglomerate controls the earth from space with an iron fist, and The People's Army, in their quest for power, doesn't care who gets caught in the crossfire. One man, together with the CEO's daughter, will use virtual reality, his cyberpunk hacking skills, and her brilliant mind to save mankind.